Expenditure on the implementation of KRUS tasks in the light of Poland’s agricultural budgets and shares in GDP in the past quarter of the century (1995–2020) - Czyżewski, Andrzej; Kata, Ryszard; Matuszczak, Anna (Ubezpieczenia w Rolnictwie – Materiały i Studia, 2022)
The objective of the article was to determine the level of expenditure of the Polish agricultural budget and expenditure on the Agricultural Social Insurance Fund (KRUS), taking into account the share of the national agricultural budget and the budget of European funds in a long term (25 years). The authors attempted to estimate the function of the trend for these time series and the degree of matching of the equations describing them. This made it possible to assess the share of KRUS expenditure in the national agricultural budget and in the general agricultural budget (i.e. national and European funds). The next step was to refer both agricultural budgets (national and increased by European funds) to the share in the national income (GDP) and the state budget. These procedures allowed to indicate how the position of KRUS in budget expenditure in the share formula and in relation to the national income and expenditure of the general agricultural budget has changed in the long term. They also made it possible to determine whether the changes in the share of expenditure in the total agricultural budget and the national budget were proportional to the changes in GDP and expenditure of the general state budget. Attempts were also made to find out whether agriculture in Poland, including KRUS, benefited from the economic growth of the country through budget expenditure and in a sustainable manner. In the conclusions, it was stated that before Poland’s accession to the European Union (EU), i.e. until 2004, agriculture was not favoured in any way, and budget expenditures were at a stable, but very low level, which did not make it possible for its restructuring. After 2004, i.e. after integration with the EU, the situation changed in terms of quantity and quality, and expenditure on agriculture, rural development and agricultural markets actually increased, stabilising at a level about 2.5 times higher than in the pre-accession period. It was noted that before the integration, the development goals were clearly undervalued in agricultural budgets, among others due to the high competitiveness of the social goal in the form of expenditure on KRUS. After 2004, the tendency to socialise expenditure in the national agricultural budget for the growth of modernisation expenditure, mainly from EU funds, was initially slowed down. This trend stabilised in the subsequent years. The share of expenditure on KRUS in the total state budget expenditures decreased by nearly one half between 2003 and 2020 (18 years). However, in recent years, i.e. 2016–2020, the socialization of the national agricultural budget has accelerated, and the share of KRUS in it has been increasing.